1994
DOI: 10.1029/94pa01444
|View full text |Cite
|
Sign up to set email alerts
|

Development of sediment drifts approaching an active plate margin under the SW Pacific Deep Western Boundary Current

Abstract: The abyssal Pacific Ocean is fed by a 1000 km wide, deep western boundary current (DWBC) that flows northward along the continental margin, east of New Zealand. Between the passive margin of Chatham Rise and the subduction zone of Kermadec Trench, a distance of 1200 km, the DWBC has formed a suite of sediment drifts over a depth range of 2200–5700 m. Airgun and 3.5‐kHz profiles record a variety of drift types that reflect regional variations in bathymetry, sediment supply, and the tectonic/volcanic framework. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 55 publications
1
38
0
Order By: Relevance
“…Observations have shown that, up to nine times a year, intense eddies can displace the isotherms associated with the SAF south from their mean position by as much as 5°of latitude. These eddies appear to extend to the abyssal ocean floor and actively move sediment (Carter & McCave 1994;Carter & Wilkin 1999). Moore et al (1999) suggested that the mean path of the PF is strongly steered by the topographic features under the Southern Ocean.…”
Section: Antarctic Circumpolar Currentmentioning
confidence: 98%
“…Observations have shown that, up to nine times a year, intense eddies can displace the isotherms associated with the SAF south from their mean position by as much as 5°of latitude. These eddies appear to extend to the abyssal ocean floor and actively move sediment (Carter & McCave 1994;Carter & Wilkin 1999). Moore et al (1999) suggested that the mean path of the PF is strongly steered by the topographic features under the Southern Ocean.…”
Section: Antarctic Circumpolar Currentmentioning
confidence: 98%
“…Once below wind-affected surface waters, particles would be entrained I orthwards, especially within the DWBC whose depth range is 2200-5500 m (Warren 1973;Carter & McCave 1994). Transport would be greatest where the flow is strongest, which is approximately along the 4000-5500 m isobaths (Fig.…”
Section: Ash Dispersalmentioning
confidence: 99%
“…Here the continental margin is part of the Hikurangi subduction system comprising an accretionary prism of anticlinal ridges and slope basins (shelf and slope), and the 2000-3000 m deep Hikurangi Trough, with a thick fill of terrigenous sediment (Lewis 1980). The trough axis is occupied by Hikurangi Channel, which meanders north to Hawke Bay before swinging east across Hikurangi Plateau to eventually debouch onto the abyssal Pacific floor, where a large fan has developed (Carter & McCave 1994). The plateau itself covers a large triangle of ocean floor (40 000 km 2 ) and has a sediment cover of turbidites overspilt from Hikurangi Channel, hemipelagites and sediment drifts, as well as widespread layers of tephra.…”
Section: Depositional Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper CPDW, at 1450-2500 m south of the rise and down to 2900 m north of the rise (McCave & Carter 1997), has temperatures of 1.8-3.0°C, salinities of 34.5-34.7%c, and includes an oxygen minimum zone. Lower CPDW is a tongue of more saline (>34.7%o) water that extends down to the bottom, and is the primary watermass of the large Deep Western Boundary Current (DWBC) in this region (Carter & McCave 1994 The main inflow of deep water is via DWBC, which enters this region from the south, passes over the Bounty Fan, across the deep eastern end of Chatham Rise, and northwestwards out across the edge of the Hikurangi Plateau. The major surface current north of the Chatham Rise is the East Cape Current (ECC) that flows south along the east coast of the North Island until it is deflected eastwards along the STF.…”
Section: Locationmentioning
confidence: 99%